Model Rumah Panggung Sehat Tahan Gempa Berbasis Komunitas di Daerah Rawan Gempa Dipesisir Danau Sentani Kabupaten Jayapura - Deasy Widyasatomo; Wika Matana (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The traditional homes of indigenous communities in Indonesia are highly vulnerable to natural disasters, particularly earthquakes, due to Indonesia's location in the Pacific Ring of Fire, which experiences high seismic activity. This situation demands the strengthening of traditional buildings to withstand potential earthquakes. Stilt houses, as a form of traditional architecture, possess characteristics that actually support earthquake resilience, such as flexible structures, the use of lightweight materials, and the application of local wisdom passed down through generations. With the development of modern construction techniques, stilt houses have the potential to become safer and more adaptable dwellings to earthquake shocks. However, indigenous communities, particularly those living in earthquake-prone areas and with lower levels of education, often face limited knowledge and skills related to the basic principles of earthquake-resistant construction. This lack of understanding results in traditional house construction without considering structural safety aspects, ultimately increasing the risk of serious damage and even collapse during an earthquake. These impacts not only threaten life but also cause significant material losses. This community service activity aims to improve the preparedness and resilience of the Sentani Indigenous community by developing earthquake-resistant stilt house models, increasing knowledge and skills in earthquake-safe house construction and maintenance, and encouraging the use of innovative technology and materials. The expected outcomes are the creation of model houses that can serve as examples and the dissemination of information on earthquake-resistant construction technology.